Challenges to dialysis treatment during the COVID-19 pandemic: a qualitative study of patients’ and experts’ perspectives - Oviedo Flores, Krystell; Stamm, Tanja; Alper, Seth L.; Ritschl, Valentin; Vychytil, Andreas (Frontiers in Psychology, 2023)
Background The global COVID-19 pandemic transformed healthcare services in ways that have impacted individual physical and psychological health. The substantial health challenges routinely faced by dialysis-dependent patients with advanced kidney disease have increased considerably during the ongoing COVID-19 pandemic but remain inadequately investigated. We therefore decided to analyze and compare the perspectives of dialysis patients on their own needs and challenges during the COVID-19 pandemic with those of their professional healthcare providers through interviews with both groups. Methods Qualitative study of seven in-center hemodialysis patients, seven peritoneal dialysis patients, seven dialysis nurses, and seven physicians at the Medical University of Vienna between March 2020 and February 2021, involving content analysis of semi-structured interviews supported by a natural language processing technique. Results Among the main themes emerging from interviews with patients were: (1) concerns about being a ‘high-risk patient’; (2) little fear of COVID-19 as a patient on hemodialysis; (3) questions about home dialysis as a better choice than in-center dialysis. Among the main themes brought up by physicians and nurses were: (1) anxiety, sadness, and loneliness of peritoneal dialysis patients; (2) negative impact of changes in clinical routine on patients’ well-being; (3) telehealth as a new modality of care. Conclusion Preventive measures against COVID-19 (e.g., use of facemasks, distancing, isolation), the introduction of telemedicine, and an increase in home dialysis have led to communication barriers and reduced face-to-face and direct physical contact between healthcare providers and patients. Physicians did not perceive the full extent of patients’ psychological burdens. Selection/modification of dialysis modality should include analysis of the patient’s support network and proactive discussion between dialysis patients and their healthcare providers about implications of the ongoing COVID-19 epidemic. Modification of clinical routine care to increase frequency of psychological evaluation should be considered in anticipation of future surges of COVID-19 or currently unforeseen pandemics.